Effect of building orientation on indoor microclimate of classroom buildings at the Kaduna State University / Markus Bulus. - Bulus, Markus (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
Current studies have discussed the significance of building orientation to the building indoor micro-climate and highlighted the need for more empirical research in other to establish the best orientation for buildings. Other scholars have argued that the impact of building orientation is insignificant and varies from one climatic region to another. This study, therefore, examines two prototype classroom buildings at the Kafanchan campus of Kaduna State University –Nigeria. The main purpose of the study is to determine the effect of building orientation on the indoor micro-climatic performance of two classroom buildings. Three Hobo Weather Data Loggers (HWDL) were used to collect data in the selected case-studies, and the third one was used as a benchmark. The study showed a remarkable difference in the indoor microclimatic conditions of the two buildings. The air temperature in case-study (B) is 1o C to 2o C lower than that of case-study (A) in all the respective time intervals. Also, 2% to 4% relative humidity difference was observed in favour of case-study (B). In conclusion, case-study (B) has demonstrated a more favourable indoor micro-climatic performance than case-study (A), and future simulation studies towards understanding the indoor micro-climatic performances of all possible building orientation options such as North-East/South-West, North-West/South-East, North/South and East/West in other to ascertain the optimum option are recommended.